2018
DOI: 10.1016/j.ijdevneu.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Cortical expression of AMPA receptors during postnatal development in a genetic model of absence epilepsy

Abstract: Childhood absence epilepsy has been associated with poor academic performance, behavioural difficulties, as well as increased risk of physical injury in some affected children. The frequent episodes of ‘absence’ arise from corticothalamocortical network dysfunction, with multifactorial mechanisms potentially involved in genetically different patients. Aberrations in glutamatergic neurotransmission has been implicated in some seizure models, and we have recently reported that reduced cortical AMPA receptor (AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…Within current literature, this mostly applies to AMPA receptors and it is the consequence of the early overestimation of NBQX as a potential selective AMPA receptor antagonist. This led to a number of reports, which attributed to AMPA receptors a number of effects in the field of epilepsies; in contrast, these effects were due to a combined activation of AMPA and kainate receptors [ 47 , 48 , 52 , 80 - 82 ].…”
Section: Ampa Receptors Seizures and Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Within current literature, this mostly applies to AMPA receptors and it is the consequence of the early overestimation of NBQX as a potential selective AMPA receptor antagonist. This led to a number of reports, which attributed to AMPA receptors a number of effects in the field of epilepsies; in contrast, these effects were due to a combined activation of AMPA and kainate receptors [ 47 , 48 , 52 , 80 - 82 ].…”
Section: Ampa Receptors Seizures and Epilepsymentioning
confidence: 99%
“…In contrast, after seizure activity, there is a reduced expression of GluA2- containing AMPA receptors. Therefore, one might argue that a loss of GluA4-containing AMPA receptors (likely GluA1/4 and GluA3/4 receptors) is linked to seizure induction, whereas a loss of GluA2-containing AMPA receptors contributes to seizure maintenance [ 82 ]. A specific loss in cortical-nRT excitation, leading to a reduced feed-forward inhibition of thalamic relay nuclei, characterizes the absence of epilepsy model of Gria4 knockout mice, which lack the GluA4 subunit [ 119 ].…”
Section: Ampa Receptors Seizures and Epilepsymentioning
confidence: 99%
“…Stargazer mice were obtained from Jackson Laboratories, USA. The breeding protocol for stargazer mice in this study was similar to our previously published work [8][9][10]. Heterozygous males were mated with either heterozygous females or homozygous females.…”
Section: Breeding Paradigm For Stargazer Micementioning
confidence: 99%
“…A lack of stargazin protein in the stargazer mouse model of absence epilepsy reduces the expression of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs) at excitatory synapses onto feed-forward inhibitory (parvalbumin expressing; PV+) interneurons of the CTC network i.e., those in the somatosensory cortex (SScortex) [ 8 , 9 , 10 , 11 ] and reticular thalamic nuclei (RTN) of the thalamus) [ 12 , 13 ]. This deficit in stargazin, a transmembrane AMPAR transporting protein (TARP), impairs excitatory input to PV+ inhibitory interneurons, thus likely reducing FFI within the cortical and thalamic microcircuits of the CTC network.…”
Section: Introductionmentioning
confidence: 99%
“…Research using the stargazer mouse model of absence epilepsy ( Barad et al, 2012 , 2017 ; Seo and Leitch, 2014 , 2015 , 2017 ; Adotevi and Leitch, 2016 , 2017 , 2019 ) has demonstrated that region-specific alterations in AMPA receptor expression in inhibitory microcircuits within the CTC network may be a key factor contributing to pathological hypersynchronous oscillatory activity in some forms of absence epilepsy. Specifically, a selective decrease in AMPA receptor expression at excitatory input synapses on RTN inhibitory interneurons from CT afferent projections (CT-RTN) but not at excitatory input synapses onto VP relay neurons (CT-VP) has been identified by Barad et al (2012) .…”
Section: Introductionmentioning
confidence: 99%